DEVELOPING A SUPPLEMENTARY MATERIAL OF MALAY TOURISM FOR VOCATIONAL STUDENTS IN PONTIANAK WEST KALIMANTAN - Rahmiani, Nur; Salam, Urai; Supardi, Iwan (Script Journal: Journal of Linguistic and English Teaching, 2018)
This study develops a supplementary material of Malay Tourism suitable for vocational tourism students (VTS) in Pontianak, Indonesia. The study focuses on the specific product phases consisting of analysis, design, development, and evaluation. The need analysis reveals that VTS need a particular material supporting tourism industry that can cover the skills of English and enhance their motivation and activities of learning English. Based on the design and development process, the product provides five units of learning materials namely introduction; cultural sites; festivals and attractions; arts and crafts; and transportation and accommodation that those parts are covering the content of Malay tourism and supporting facilitation. All of the components represent the findings of the analysis process. The product also provides appropriate pictures, instructional guides, maps, grammar guide, and words of wisdom in which packed in a travel guidebook. The evaluation is conducted to secure the suitability and the responses of the participants using the validator, the teacher and students questionnaire that this supplementary material meets the need for the tenth-year students at SMK Pariwisata CBK Pontianak. The evaluation also provides the feedback from the participants in the revision process.